A hybrid financial performance evaluation model for wealth management banks following the global financial crisis. Issue 1 (2nd January 2016) - Chang, Shun-Chiao; Tsai, Pei-Hsuan
Abstract: The study constructs a hybrid approach to financial performance evaluation for wealth management (WM) banks affected by the global financial crisis from the middle of 2007 into 2008 utilizing an analytic hierarchy process (AHP) and the VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR). Five aspects of multi-criteria group decision making including service, performance, professionalism, risk control, and consumers' confidence (SPPRC) reveal that consumers' confidence, risk control and service are the top three key factors for Taiwan's seven main WM banks in evaluating the performance of banking managers.